Discovery and characterization of New Delhi metallo-β-lactamase-1 inhibitor peptides that potentiate meropenem-dependent killing of carbapenemase-producing Enterobacteriaceae. (26th June 2020) - Kazi, Misha I; Perry, Blair W; Card, Daren C; Schargel, Richard D; Ali, Hana B; Obuekwe, Victor C; Sapkota, Madhab; Kang, Katie N; Pellegrino, Mark W; Greenberg, David E; Castoe, Todd A; Boll, Joseph M
Abstract: Objectives: Metallo-β-lactamases (MBLs) are an emerging class of antimicrobial resistance enzymes that degrade β-lactam antibiotics, including last-resort carbapenems. Infections caused by carbapenemase-producing Enterobacteriaceae (CPE) are increasingly prevalent, but treatment options are limited. While several serine-dependent β-lactamase inhibitors are formulated with commonly prescribed β-lactams, no MBL inhibitors are currently approved for combinatorial therapies. New compounds that target MBLs to restore carbapenem activity against CPE are therefore urgently needed. Herein we identified and characterized novel synthetic peptide inhibitors that bound to and inhibited NDM-1, which is an emerging β-lactam resistance mechanism in CPE. Methods: We leveraged S urface L ocalized A ntimicrobial displaY (SLAY) to identify and characterize peptides that inhibit NDM-1, which is a primary carbapenem resistance mechanism in CPE. Lead inhibitor sequences were chemically synthesized and MBCs and MICs were calculated in the presence/absence of carbapenems. Kinetic analysis with recombinant NDM-1 and select peptides tested direct binding and supported NDM-1 inhibitor mechanisms of action. Inhibitors were also tested for cytotoxicity. Results: We identified approximately 1700 sequences that potentiated carbapenem-dependent killing against NDM-1 Escherichia coli . Several also enhanced meropenem-dependent killing of other CPE. Biochemical characterization of a subset indicated the peptides penetrated the bacterial periplasm and directly bound NDM-1 to inhibit enzymatic activity. Additionally, each demonstrated minimal haemolysis and cytotoxicity against mammalian cell lines. Conclusions: Our approach advances a molecular platform for antimicrobial discovery, which complements the growing need for alternative antimicrobials. We also discovered lead NDM-1 inhibitors, which serve as a starting point for further chemical optimization.